Pembuatan E-Catalog berbasis QR-Code mendukung digitalisasi Desa Krampon, Torjun Sampang - Etistika Yuni Wijaya; Nuru Aini; Renita Solehah; Solehah Solehah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Information Communication Technology (ICT) for changes in life and economic growth in every region. Villages are a very important part in determining the success of development and are in direct contact with the community, especially in public services. The problems that arise and are faced are the low level of skill of village officials with the demands of a more dynamic society and the records management system which is still conventional which triggers high risks. In line with the reform agenda of the Ministry of State Apparatus Empowerment and Bureaucratic Reform, every individual and organization is required to develop themselves in order to improve community services. Conventional administrative and archive management must be changed to system-based and digital. Apart from that, the village also needs to publicize all its potential so that it becomes easier for the public to get information about the village, in addition to the need to carry out public transparency. Therefore, we are present at the Torjun Thematic KKN 2023 community service program, especially in Krampon village, Sampang, to provide a solution to resolve this problem by providing assistance in developing a village website and an information system to manage data in the village using QR-Code as well as training in using QR-Code. Code with society. Apart from that, this activity was carried out in order to increase the abilities and skills of village officials by providing workshops and outreach. The aim of implementing this program is to provide a medium to publicize all the potential that the village has, orderly digital-based administrative management and increase the capabilities and skills of the village apparatus. As a result of the program, there is an increase in the quality of services to the community and publications.